The Development Of Nursing Informatics Research On Patient Safety: a Bibliometric Perspective - Suganda, Tomy; Amaliyah, Eli; Rahmi Galleryzki, Annisa; Suwahyu, Romy; Ghozali, Imam (IKES Payung Negeri Pekanbaru, 2025)
Background: Patient safety remains a global health priority and a key indicator of healthcare quality. Over the past decade, nursing informatics has emerged as a critical discipline to enhance patient safety by integrating electronic health records (EHRs), clinical decision support systems (CDSS), and digital health innovations into nursing practice. Aim: This study employed a bibliometric analysis to map the scientific landscape of nursing informatics research on patient safety between 2015 and 2025. Methods: Data were retrieved from the Scopus database and analyzed using Bibliometrix R and VOSviewer, following PRISMA guidelines. Results: A total of 339 publications were identified, with an annual growth rate of 4.14% and an average of 11.96 citations per document, indicating a moderate to high research impact. The analysis revealed highly productive authors such as Bowles, Carrington, and Topaz, and leading institutions including the University of Pennsylvania and Harvard Medical School. Keyword analysis demonstrated a diversification of themes, with dominant clusters centered on EHRs, patient safety, nursing informatics, and CDSS, alongside emerging topics such as digital health and artificial intelligence. Furthermore, international collaboration accounted for 15.04% of publications, highlighting the multidisciplinary and global nature of the field. Discussion: These findings underscore the growing recognition of nursing informatics as a cornerstone in advancing evidence-based nursing practice and improving patient safety outcomes. The study provides a comprehensive overview of research trends, identifies knowledge gaps, and offers strategic directions for policy, education, and future investigations in nursing informatics.